Initial examination of the mental health disorders: screening instrument for athletes - Donohue, Brad; Scott, Jesse; Goodwin, Grace; Barchard, Kimberly A.; Bohall, Greg; Allen, Daniel N. (Frontiers in Psychology, 2023)
There is a need to psychometrically develop assessment instruments capable of screening mental health disorders in collegiate athlete populations. The current study was conducted to determine reliability, validity and clinical utility of the Mental Health Disorders Screening Instrument for Athletes (MHDSIA). Factor analysis determined a single factor with good internal consistency, and this factor was positively correlated with an established measure of psychiatric symptomology (i.e., concurrent validity). Clinical cutoff scores were determined using Receiver Operating Characteristic (ROC) analyses to assist appropriate mental health referrals. Future recommendations for mental health screening are discussed.